Unveiling a CD70-positive subset of cancer-associated fibroblasts marked by pro-migratory activity and thriving regulatory T cell accumulation. (3rd July 2018) - Jacobs, Julie; Deschoolmeester, Vanessa; Zwaenepoel, Karen; Flieswasser, Tal; Deben, Christophe; Van den Bossche, Jolien; Hermans, Christophe; Rolfo, Christian; Peeters, Marc; De Wever, Olivier; Lardon, Filip; Siozopoulou, Vasiliki; et al.
ABSTRACT: Cancer-associated fibroblasts (CAFs) are involved in the proliferative and invasive behavior of colorectal cancer (CRC). Nonetheless, CAFs represent a heterogeneous population with both cancer-promoting and cancer-restraining actions, lacking specific markers to target them. Expression of the immune checkpoint molecule CD70 is normally limited to cells of the lymphoid lineage. Instead, tumor cells hijack CD70 to facilitate immune evasion by increasing the amount of suppressive regulatory T cells (Tregs). The aim of this study was to explore CD70 expression patterns in CRC, not merely focusing on the tumor cells, but also taking the tumor stromal cells into account. We have analyzed the prognostic value of CD70 expression by immunohistochemistry in CRC specimens and its relationship with well-known fibroblast markers and Tregs. In addition, in vitro experiments were conducted to unravel the role of CD70-positive CAFs on migration and immune escape. We reveal prominent expression of CD70 on a specific subset of CAFs in invasive CRC specimens. Cancer cells show almost no expression of CD70. The presence of CD70-positive CAFs proved to be an independent adverse prognostic marker. Functionally, CD70-positive CAFs stimulated migration and significantly increased the frequency of naturally occurring Tregs. In conclusion, we have identified the expression of CD70 on CAFs as a novel prognostic marker for CRC. We have found evidence of a cross talk between CD70 + CAFs and naturally occurring Tregs, paving the way towards immune escape. As such, this study provides a strong rationale for the exploration of CD70-targeting antibodies in CRC.